Formulation and evaluation of floating tablets of esomeprazole - D.Sumith Reddy; Ganesh Kumar Gudas (International Journal of Pharmacy and Analytical Research, 2017)
The present study outlines a systematic approach for designing and development of Esomeprazole floating tablets to enhance the bioavailability and therapeutic efficacy of the drug. Floating tablets of Esomeprazole have shown sustained release thereby proper duration of action at a particular site and are designed to prolong the gastric residence time after oral administration. Different formulations were formulated by using wet granulation technique. A floating drug delivery system (FDDS) was developed by u sing sodium bicarbonate as gas-forming agent and chitosan, compritol 888ato, HPMC K15 M as polymers. The prepared tablets were evaluated in terms of their physical characteristics, precompression parameters, in vitro release and buoyancy lag time. The results of the in vitro release studies showed that the optimized formulation (F6) could sustain drug release for 12 hrs by using HPMC K15M in the concentration of 60 mg. The in vitro drug release followed zero order kinetics. The stability of optimized formulation (F6) was known by performing stability studies for three months at accelerated condition of 40 0C±75%RH on optimized formulation. The F6 formulation was found to be stable with no change.